Contextualized handbook of play-based activities in mathematics for kindergarten - Abadilla, Myrell O. (Laog City : [s.n.], 2018)
This descriptive study developed a validated contextualized handbook of play-based activities in Mathematics for Kindergarten. Specifically, it determined the extent of need for enrichment materials as perceived by the kindergarten teachers. This was based from the standards and competencies for five-year old Filipino children of the K to 12 program. The level of competency of the kindergarten learners in mathematics was also assessed using the School Readiness Year-End Assessment (SReYA).
Bibliography: pages 231-234.
CHED-La Union
Keywords: Kindergarten -- Mathematics